2019
DOI: 10.1371/journal.pone.0223341
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide DNA methylation profiling identifies specific epigenetic features in high-risk cutaneous squamous cell carcinoma

Abstract: Cutaneous squamous cell carcinoma (cSCC) is the second most common skin cancer. Although most cSCCs have good prognosis, a subgroup of high-risk cSCC has a higher frequency of recurrence and mortality. Therefore, the identification of molecular risk factors associated with this aggressive subtype is of major interest. In this work we carried out a global-scale approach to investigate the DNA-methylation profile in patients at different stages, from premalignant actinic keratosis to low-risk invasive and high-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…Recently, a global-scale approach to investigate the DNA-methylation profile in patients at different stages (i.e., AK, low-risk invasive, high-risk nonmetastatic, and metastatic cSCC) identified a minimal methylation signature to discriminate different stages, especially distinguishing low-risk vs. high-risk stages. Moreover, a prognostic prediction model in cSCC patients identified a methylation signature able to predict the overall survival of patients [ 119 ].…”
Section: Pathogenesis Of Csccmentioning
confidence: 99%
“…Recently, a global-scale approach to investigate the DNA-methylation profile in patients at different stages (i.e., AK, low-risk invasive, high-risk nonmetastatic, and metastatic cSCC) identified a minimal methylation signature to discriminate different stages, especially distinguishing low-risk vs. high-risk stages. Moreover, a prognostic prediction model in cSCC patients identified a methylation signature able to predict the overall survival of patients [ 119 ].…”
Section: Pathogenesis Of Csccmentioning
confidence: 99%
“…In cutaneous melanoma, it was demonstrated that promoter hypomethylation and intragenic hypermethylation of specific genes are associated with tumor aggressiveness due to the alteration of extracellular matrix components and the upregulation of matrix metalloproteinases [98][99][100]. This highlights the clinical potential of deregulated methylation status as a hallmark for carcinogenesis, allowing the recognition of various methylation patterns as biomarkers for diagnosis and prognosis [101] (Table 1). Methylation studies focusing on cSCC, have demonstrated various patterns.…”
Section: Cpg Island Methylation (Cim)mentioning
confidence: 99%
“…In detail, they demonstrated a differential methylation status between the two pathological stages, with low-risk SCCs being hypomethylated and high-risk SCCs hypermethylated. According to the authors, this finding may suggest a sequential approach of SCC formation, where UV-exposure leads to hypomethylation and thus foretells the premalignant and low-risk stages of cSCC, while advanced stages of SCC present a hypermethylated status [101]. As regards the evaluation of the methylation status of BCC, Goldberg et al presented the FHIT promoter to be hypomethylated [114], while Heitzer et al found the hypermethylated PTCH promoter only in a small number of cases [115].…”
Section: Cpg Island Methylation (Cim)mentioning
confidence: 99%
“…Having confirmed that differential FILIP1L methylation and expression is also present in human cSCC, we evaluated its clinical relevance in humans using Infininium MethylationEPIC data provided by Herv as-Marín et al for 10 low (initial invasive carcinoma) and 8 high-risk (high-risk non-metastatic carcinoma and metastatic carcinoma) samples [33]. Note that a high-risk assessment is associated with a higher frequency of local recurrence, lymph node metastasis and significant morbidity and mortality and thus helps identifying patients with poor outcomes.…”
Section: Differential Methylation At the Filip1l Locus Affects Filip1l Expressionmentioning
confidence: 96%